Basis Of Knowledge And Criteria Of Truth From Western And Islamic Perspectives - Suchi Nurul Khofifah; Muhammad Nawawi; Azizah Hanum OK (Sean Institute, 2025)
The purpose of this research is to explain the basis of knowledge, the measurement of truth, the criteria for truth from Western and Islamic perspectives. The type of research used in this study is a literature study using descriptive analysis methods. This research was carried out by collecting various kinds of information and studying various kinds of literature related to the basic knowledge and criteria for truth from Islamic and Western perspectives. The results of this research show that the basic meaning of knowledge is that truth is something that is real and in accordance with facts and is relative. This means that what one person thinks is right, may not necessarily be what someone else thinks is right. The measure of truth can be proven by several theories including correspondence, correlation, phlegmatic, performative and consensus theories. From an Islamic perspective, religious truth theory, aql , siddiq . The criteria for truth in the Western perspective are epistemology, ontology and semantics and the criteria according to the Islamic perspective are the Koran and the hadith of the prophet Muhammad .